Teologiczny aspekt problematyki Boga we współczesnej polskiej poezji (na tle ogólnoświatowych tendencji literatury pięknej drugiej połowy XX wieku) - Szymik, Jerzy (Śląskie Studia Historyczno-Teologiczne, 1998)
The relationship „theology – belles letters” has its rich history. Having experience of common roots (in the word), stages of co-operation and mutual distrust, reluctance the end of the second millenium can be time of „renewing a covenant”. In XX century Polish literature is a good example of practising many threads of so-called literary theology. Being inspired most often – but not only by the poetry written in English, modern Polish poetry includes thematic-problem ranges (aksjology, a figure of paradox, metaphysics). It is in such ranges that theology in belles-lettres can be found. The works of Herbert, Twardowski and Miłosz these are the signs of such a phenomenon. It is in such a way that the „theo-logical” identity of modern Polish art of the word has been achieved.